2004
DOI: 10.1007/s00170-002-1520-y
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of machining performance of STAVAX with PCBN tools

Abstract: A study was undertaken to investigate the wear characteristics of polycrystalline cubic boron nitride (PCBN) cutting tools and surface integrity during machining of STAVAX (specialised stainless steel) with and without coolant. Plastic deformation and formation of overtempered martensite and white layer (untempered martensite) were the dominant subsurface and surface defects. It was found that decreasing the hardness of the STAVAX from 55 HRC to 40 HRC could result in fracture on the flank face, leading to a d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…Recently, we have investigated the machinability of STAVAX using the ultra-precision and conventional turning machines, and observed changes in the tool wear as the hardness of the alloy was increased from 40 to 55 HRC [15][16][17]. It was found that the cutting parameters such as speed, depth of cut and feed rate had significant influence on the effect of the hardness of the alloy on the tool wear.…”
Section: Introductionmentioning
confidence: 98%
“…Recently, we have investigated the machinability of STAVAX using the ultra-precision and conventional turning machines, and observed changes in the tool wear as the hardness of the alloy was increased from 40 to 55 HRC [15][16][17]. It was found that the cutting parameters such as speed, depth of cut and feed rate had significant influence on the effect of the hardness of the alloy on the tool wear.…”
Section: Introductionmentioning
confidence: 98%
“…It was postulated that the micro-holes containing molybdenum disulphide acted as a source of lubricant. Results obtained in earlier work by Liew et al (2003Liew et al ( , 2004b, Ding et al (2002) showed that in turning of stainless steel at low speeds with carbide and PCBN tools where the tool wear was governed by fracture and abrasive wear, liquid paraffin oil and cyclomethicone sprayed in small quantity in mist form was effective in reducing the tool wear and improving the surface finish. More recently, Deng et al (2012) studied the performance of conventional WC/Co carbide tools and textured WC/Co carbide tools filled with molybdenum disulphide in dry machining of steel.…”
Section: Solid Lubricantmentioning
confidence: 91%
“…Both the conventionally machined workpiece and that of LAM have virtually identical hardness profiles, exhibiting a slight reduction of the hardness from the surface to a depth of 75-100 mm. It is not unusual in stainless steels to report a deformed layer of 10 mm or less [28], which is too small to measure with the hardness tester.…”
Section: Microstructural Analysismentioning
confidence: 99%